Anti-diarrheal activities of phytol along with its possible mechanism of action through in-vivo and in-silico models - Islam, Muhammad Torequl; Rahman, Mohammad Asikur; Saeed, Maria; Ul-Haq, Zaheer; Alam, Md. Jahir; Mondal, Milon; Hossain, Rajib; Mubarak, Mohammad S.; Salehi, Bahare; Setzer, William N.; Abdull Razis, Ahmad Faizal; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
Phytol (PHY), a chlorophyll-derived diterpenoid, exhibits numerous pharmacological properties, including antioxidant, antimicrobial, and anticancer activities. This study evaluates the anti-diarrheal effect of phytol (PHY) along with its possible mechanism of action through in-vivo and in-silico models. The effect of PHY was investigated on castor oil-induced diarrhea in Swiss mice by using prazosin, propranolol, loperamide, and nifedipine as standards with or without PHY. PHY at 50 mg/kg (p.o.) and all other standards exhibit significant (p < 0.05) anti-diarrheal effect in mice. The effect was prominent in the loperamide and propranolol groups. PHY co-treated with prazosin and propranolol was found to increase in latent periods along with a significant reduction in diarrheal section during the observation period than other individual or combined groups. Furthermore, molecular docking studies also suggested that PHY showed better interactions with the Î±- and Î²-adrenergic receptors, especially with Î±-ADR1a and Î²-ADR1. In the former case, PHY showed interaction with hydroxyl group of Ser192 at a distance of 2.91í…, while in the latter it showed hydrogen bond interactions with Thr170 and Lys297 with a distance of 2.65 and 2.72í…, respectively. PHY exerted significant anti-diarrheal effect in Swiss mice, possibly through blocking Î±- and Î²-adrenergic receptors.